Use of a Small Unmanned Aerial System for the SR‐530 Mudslide Incident near Oso, Washington. Issue 4 (4th May 2015) - Murphy, Robin R.; Duncan, Brittany A.; Collins, Tyler; Kendrick, Justin; Lohman, Patrick; Palmer, Tamara; Sanborn, Frank
Abstract : The Center for Robot‐Assisted Search and Rescue deployed three commercially available small unmanned aerial systems (SUASs)—an AirRobot AR100B quadrotor, an Insitu Scan Eagle, and a PrecisionHawk Lancaster—to the 2014 SR‐530 Washington State mudslides. The purpose of the flights was to allow geologists and hydrologists to assess the eminent risk of loss of life to responders from further slides and flooding, as well as to gain a more comprehensive understanding of the event. The AirRobot AR100B in conjunction with PrecisionHawk post‐processing software created two‐dimensional (2D) and 3D reconstructions of the inaccessible "moonscape" region of the slide and provided engineers with a real‐time remote presence assessment of river mitigation activities. The AirRobot was able to cover 30–40 acres from an altitude of 42 m (140 ft) in 48 min of flight time and generate interactive 3D reconstructions in 3 h on a laptop in the field. The deployment is the 17th known use of SUAS for disasters, and it illustrates the evolution of SUASs from tactical data collection platforms to strategic data‐to‐decision systems. It was the first known instance in the United States in which an airspace deconfliction plan allowed a UAS to operate with manned vehicles in the same airspace during a disaster. It also describes how public concerns over SUAS safety and privacy led to the cancellation of initial flights. The deployment provides lessons on operational considerations imposed by the terrain, trees, power lines, and accessibility, and a safe human:robot ratio. The article identifies open research questions in computer vision, mission planning, and data archiving, curation, and mining.